Changes in the Levels of Methionine Adenosyltransferase, Methionine Sulfoxide Reductase A, and Thioredoxin are Associated with Oxidative Stress in Patients with Hyperthyroidism - Marwa A. Al-Badrany; Luay A. Al-Helaly (Diyala Journal of Medicine, 2025)
Background: Hyperthyroidism is associated with increased oxidative stress and alterations in enzymatic and non-enzymatic antioxidant systems. Methionine adenosyltransferase (MAT) plays a key role in cellular metabolism and may be involved in redox homeostasis in thyroid disorders. Objectives: This study aimed to evaluate the levels of MAT and investigate its association with selected enzymatic and non-enzymatic oxidative stress markers in patients with hyperthyroidism. Patients and Methods: A total of 90 blood serum samples were collected from patients with hyperthyroidism and compared with 50 healthy controls. Enzymatic markers measured included methionine sulfoxide reductase A (MsrA), thioredoxin (Trx), catalase (Cat), myeloperoxidase (MPO), lactoperoxidase (LP), xanthine oxidase (XO), glutathione S-transferase (GST), and senescence marker protein-30 (SMP-30). Non-enzymatic markers included glutathione (GSH), uric acid (UA), albumin (Alb), malondialdehyde (MDA), and peroxynitrite (ONOO⁻). Results: Compared to healthy controls, patients with hyperthyroidism showed a significant increase in MAT, Cat, XO, GST, Trx, and LP levels, while SMP-30 was significantly decreased. Among non-enzymatic parameters, MDA and ONOO⁻ were significantly elevated, and albumin levels were decreased. No significant changes were found in the remaining markers. MAT showed a direct correlation with SMP-30, MPO, MsrA, UA, ONOO⁻, and Alb, and an inverse relationship with Cat, XO, and GSH. No correlation was observed between MAT and GST, LP, or Trx. Conclusion: The findings suggest a strong association between MAT activity and oxidative stress in patients with hyperthyroidism. The observed changes point to metabolic imbalances and compromised antioxidant defense mechanisms in these patients. Keywords: Hyperthyroidism, Enzyme, Methionine adenosyltransferase, Methionine sulfoxide reductase A, Thioredoxin.